The Role of School Management in Supporting Successful Curriculum Implementation - Azizah, Salsabila; Arwan Saputra; Benny Alidarsil; Mudasir (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the role of school management in supporting the successful implementation of the curriculum through a qualitative approach using a literature study method. School management is viewed as a strategic factor that determines the effectiveness of curriculum implementation at the school level, particularly in response to dynamic educational policies and demands. This study analyzes various academic sources, including peer-reviewed journal articles, reference books, and relevant scholarly publications related to school management and curriculum implementation. The data were analyzed thematically through stages of data collection, reduction, presentation, and synthesis of findings from the literature. The results indicate that successful curriculum implementation is strongly influenced by key school management functions, including systematic curriculum planning, effective school leadership, support for teachers through academic supervision and professional development, management of human resources and school facilities, the development of a supportive school culture, and continuous monitoring and evaluation processes. The literature also highlights that school management acts as a crucial link between curriculum policy and classroom instructional practices. Without strong and integrated school management, curriculum implementation may not achieve its intended objectives.